Mainstreaming Religious Moderation Learning in Early Childhood Educational Institutions in Pekalongan City - A.Tabi'in; Zulkipli Lessy; Suhadi (Edukasia Islamika : Jurnal Pendidikan Islam, 2025)
Early childhood education (Pendidikan Anak Usia Dini, hereafter PAUD) institutions play a vital role in shaping children's character, including fostering inclusive and tolerant attitudes toward diversity. As religious moderation gains prominence as a national policy agenda, it becomes essential to understand how such values are internalized and practiced within early learning environments. This study investigates how religious moderation is understood and implemented by educators, and how teaching strategies and parental involvement contribute to its cultivation in children’s lives. Using a qualitative phenomenological approach, data were gathered through observations, document analysis, and in-depth interviews with teachers, principals, parents, and educational staff from four early childhood education institutions in Pekalongan City. Thematic analysis, guided by Albert Bandura’s Social Learning Theory, was conducted using an inductive approach to interpret participants’ social and pedagogical experiences. The findings reveal that religious moderation education promotes inclusive, empathetic, and tolerant behaviors among young children. These values are fostered through role-play, storytelling, collaborative activities, and teacher-modeled interactions. Instructional methods are contextualized using national narratives, local Islamic traditions, and daily character-building practices. Teachers observed that children became more open in interacting with peers from diverse backgrounds. Parental involvement reinforces these values at home through open dialogue and responsiveness to children’s curiosity about differences. The synergy between school-based learning and family support forms a solid foundation for the development of moderate religious attitudes and respect for diversity from an early age.